Digitalization of "English for Informatics" for Generation Z Students: A Flipbook-Based Learning Media - Tangkelangi, Nuur Insan; Upa, Rahmawati; Yasir, Fajar Novriansyah (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
Informatics students currently face challenges in mastering English, which is crucial for keeping up with developments in computer science, as this language serves as the primary instructional medium. Previous research has shown that, despite its importance, the level of English proficiency among students at our campus remains low. This research has identified students' needs and developed teaching materials; however, these materials are still presented in conventional printed modules and do not fully address needs such as pronunciation. In this study, the researchers designed a flipbook-based learning media that integrates audio, images, and videos to meet the diverse needs of students in learning English. This media is also tailored to align with the expectations of Generation Z, who are very familiar with technology. The method used in the design process is Research and Development (RnD) with the ADDIE development model (Analysis, Design, Develop, Implementation, Evaluation). The results indicate that the English for Informatics flipbook-based learning media consists of seven chapters, equipped with multimedia elements and gamification concepts. Validation from subject matter and media experts categorizes this media as "very suitable for use." Additionally, student response analysis shows very positive feedback regarding the use of this flipbook, indicating significant potential to enhance English language skills among Informatics students at our campus.